First-in-Human Trial of EphA2-Redirected CAR T-Cells in Patients With Recurrent Glioblastoma: A Preliminary Report of Three Cases at the Starting Dose - Lin, Qingtang; Ba, Teer; Ho, Jinyuan; Chen, Dandan; Cheng, Ye; Wang, Leiming; Xu, Geng; Xu, Lixin; Zhou, Yiqiang; Wei, Yukui; Li, Jianqiang; Ling, Feng (Frontiers in Oncology, 2021)
Glioblastoma is the most common primary brain malignancy with limited treatment options. EphA2 is a tumor-associated-antigen overexpressed in glioblastoma. Pre-clinical studies have demonstrated the promise of EphA2-redirected CAR T-cells against glioblastoma. We conduct the first-in-human trial of EphA2-redirected CAR T-cells in patients with EphA2-positive recurrent glioblastoma and report the results of three patients enrolled as the first cohort receiving the starting dosage (1×106 cells/kg). A single infusion of EphA2-redirected CAR T-cells was administrated intravenously, with the lymphodepletion regimen consisting of fludarabine and Cyclophosphamide. In two patients, there was grade 2 cytokine release syndrome accompanied by pulmonary edema, which resolved completely with dexamethasone medication. Except that, there was no other organ toxicity including neurotoxicity. In both the peripheral blood and cerebral-spinal-fluid, we observed the expansion of CAR T-cells which persisted for more than four weeks. In one patient, there was a transit diminishment of the tumor. Among these three patients, one patient reported SD and two patients reported PD, with overall survival ranging from 86 to 181 days. At the tested dose level (1×106 cells/kg), intravenously infusion of EphA2-rediretected CAR T-cells were preliminary tolerable with transient clinical efficacy. Future study with adjusted dose and infusion frequency of CAR T-cells is warranted.